Experimental and numerical investigations on the dynamic response of turbine blades with tip pin dampers. (September 2016) - Zucca, S.; Berruti, T.; Cosi, L.
Abstract: Friction dampers are used to reduce vibration amplitude of turbine blades. The dynamics of these assemblies (blades + dampers) is nonlinear and the analysis is challenging from both the experimental and the numerical point of view. The study of the dynamics of blades with a tip damper is the aim of the present paper. The blades with axial-entry fir tree attachment carry a damper in a pocket between the blade covers. Pin dampers significantly affect the resonance frequency of the first blade bending mode and introduces non linearity due to friction contacts. A test rig, made of two blades held in a fixture by an hydraulic press with one damper between the blades was used for the experimental activity. Three different types of dampers (cylindrical, asymmetrical, wedge) have been experimentally investigated and experiments have shown that asymmetrical damper performs better than the others. The response of the blades with the asymmetrical damper was then simulated with a non linear code based on the Harmonic Balance Method (HBM). In the analysis, both the blade and the damper are modelled with the Finite Elements and then the matrices reduced with the Craig- Bampton Component Mode Synthesis (CB-CMS), while the periodical contact forces are modelled with state-of-the-art node-to-node contact elements. Numerical analysis has shown a strong influence of the actual extent of the contact area on the dynamics of the assembly. A model updating process was necessary. In the end, the numerical predictions match very well with the experimental curves.